2012
DOI: 10.1007/s00259-011-2008-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution, radiation dosimetry and scouting of 90Y-ibritumomab tiuxetan therapy in patients with relapsed B-cell non-Hodgkin’s lymphoma using 89Zr-ibritumomab tiuxetan and PET

Abstract: PurposePositron emission tomography (PET) with 89Zr-ibritumomab tiuxetan can be used to monitor biodistribution of 90Y-ibritumomab tiuxetan as shown in mice. The aim of this study was to assess biodistribution and radiation dosimetry of 90Y-ibritumomab tiuxetan in humans on the basis of 89Zr-ibritumomab tiuxetan imaging, to evaluate whether co-injection of a therapeutic amount of 90Y-ibritumomab tiuxetan influences biodistribution of 89Zr-ibritumomab tiuxetan and whether pre-therapy scout scans with 89Zr-ibrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 22 publications
2
86
0
Order By: Relevance
“…However, the use of 89 Zr is preferred mainly for tracers with slow kinetics, such as antibodies, because of its long radioactive half-life (3.3 d). This longer half-life inherently results in higher effective doses, such as 0.55 6 0.07 mSv/MBq for 89 Zr-ibritumomab tiuxetan (24). For the present patient group, the absorbed doses due to 68 Ga-ABY-025 should also be seen through the perspective that diagnostic CT scans of the thorax and abdomen will give comparable or higher effective doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of 89 Zr is preferred mainly for tracers with slow kinetics, such as antibodies, because of its long radioactive half-life (3.3 d). This longer half-life inherently results in higher effective doses, such as 0.55 6 0.07 mSv/MBq for 89 Zr-ibritumomab tiuxetan (24). For the present patient group, the absorbed doses due to 68 Ga-ABY-025 should also be seen through the perspective that diagnostic CT scans of the thorax and abdomen will give comparable or higher effective doses.…”
Section: Discussionmentioning
confidence: 99%
“…Rizvi et al (2) reported that, for 89 Zr-ibritumomab tiuxetan, the liver was the organ with the highest absorbed dose (1.36 6 0.58 mGyÁMBq 21 ), followed by the spleen (1.04 6 0.16 mGyÁMBq 21 ), kidneys (0.75 6 0.06 mGyÁMBq 21 ), lungs (0.63 6 0.11 mGyÁMBq 21 ), and RM (0.46 6 0.05 mGyÁMBq 21 ), whereas the effective dose was found to be 0.55 6 0.07 mSvÁMBq 21 . Borjesson et al (19) in a radiation dosimetry study of 89 Zr-cmAb U36 found the highest absorbed dose for the liver (1.30 6 0.34 mSvÁMBq 21 ), followed by the kidneys (1.00 6 0.30 mSvÁMBq 21 ), lungs (0.79 6 0.26 mSvÁMBq 21 ), and spleen (0.72 6 0.18 mSvÁMBq 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a recent study showed that the biodistributions of 89 ZrDf-cetuximab and 88 Y-DOTA-cetuximab ( 88 Y as a substitute for 90 Y) were comparable for all organs (1). Another study from the same group demonstrated nearly identical biodistributions of 89 Zribritumomab and 90 Y-ibritumomab (2). Recently, the effect of radioimmunotherapy using 90 Y-cetuximab (combined with external-beam irradiation) on local tumor control in vivo was examined in 3 human squamous cell carcinoma models (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it can easily and stably be coupled to monoclonal antibodies (2). To date, all 89 Zr-monoclonal antibody PET/CT studies that have been reported were performed within a single center (3)(4)(5). More recently, several multicenter studies have been initiated.…”
mentioning
confidence: 99%